Luhmann explained from souls to systems - Moeller, Hans-Georg 1964- (Chicago Open Court, 2006)
"An introduction to Niklas Luhmann's social systems theory. Discusses key concepts and relevant philosophical issues, and presents a case study. English-language translations of three of Luhmann's essays and bibliographies of works by and on Luhmann are included"--Provided by publisher.
Introduction -- Part 1. A new way of thinking about society. What is social systems theory? ; What is real? ; What happens to the human being? ; What can be done? -- Part 2. Mass media. The mass media as a system ; Beyond manipulation ; The reality of the mass media ; Individuality and freedom -- Part 3. Philosophical contexts. Kant ; Hegel ; Marx ; Husserl ; Habermas ; Postmodernity, deconstruction, and techno-theory -- Conclusion: From metanarrative to supertheory.
Keywords: Luhmann, Niklas -- 1927-1998.; Social systems; Social systems -- Philosophy; Mass media -- Social aspects